2017
DOI: 10.1080/08958378.2017.1318985
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure/function variation in cultured differentiated human nasal epithelium associated with acute single exposure to tobacco smoke or E-cigarette vapor

Abstract: Objective Mucociliary clearance sustains a baseline functionality and an “on demand” capability to upregulate clearance upon irritant exposure involving mucus hypersecretion and accelerated ciliary beat frequency (CBF) modulated by nitric oxide (NO). This study characterized these elements as well as cellular and exogenous NO concentrations subsequent to a single exposure to tobacco smoke (TS) or e-cigarette vapor (EV) on cultured human airway epithelium. Materials and methods Air-liquid interface (ALI) airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…Cultures appropriated for such studies can be readily manipulated experimentally and multiplexed for replicate or extended studies. In the present study, we detected in vitro concentrations of NO in control cultures that were consistent with other studies performed in this laboratory (Carson et al 2017). Moreover, our studies indicated that cohort cultures propagated in the presence of IL-13, and the absence of an eosinophilic compartment were sufficiently stimulated to excrete an average of greater than tenfold the NO levels seen in control cultures.…”
supporting
confidence: 93%
“…Cultures appropriated for such studies can be readily manipulated experimentally and multiplexed for replicate or extended studies. In the present study, we detected in vitro concentrations of NO in control cultures that were consistent with other studies performed in this laboratory (Carson et al 2017). Moreover, our studies indicated that cohort cultures propagated in the presence of IL-13, and the absence of an eosinophilic compartment were sufficiently stimulated to excrete an average of greater than tenfold the NO levels seen in control cultures.…”
supporting
confidence: 93%
“…Furthermore, previous studies showed that doses ~20-fold higher than effective in vitro doses are optimal for nebulized treatments in sheep (55,56) . A small remaining TMV decrease may be related to direct effects of PG/VG due to its physiochemical properties that can hinder ciliary beating as recently reported (57,58).…”
Section: Discussionmentioning
confidence: 68%
“…35,36 In vitro analysis found that exposure of airway epithelium cells to either diacetyl or 2,3-pentanedione resulted in disruption of genes that direct cilia biogenesis and directly resulted in impaired ciliary number and function. 37,38 Cinnamaldehyde, 39,40 benzaldehyde, 41 2,5-dimethylpyrazine (chocolate flavoring), 42 among other flavorants, 43 have adverse respiratory effects as well.…”
Section: Science Behind the Harms Of Vapingmentioning
confidence: 99%